Predicting competitive alpine skiing performance by multivariable statistics—the need for individual profiling - Nilsson, R.; Theos, A.; Lindberg, A.-S.; Malm, C. (Frontiers in Sports and Active Living, 2025)
Introduction: Predicting competitive alpine skiing performance using conventional statistical methods has proven challenging. Many studies assessing the relationship between physiological performance and skiing outcomes have employed statistical methods of questionable validity. Furthermore, the reliance on Fédération Internationale de Ski (FIS) points as a performance outcome variable presents additional limitations due to its potential unreliability in reflecting short-term, sport-specific performance. These factors complicate the selection of appropriate tests and the accurate prediction of competitive outcomes.